HUBUNGAN KEPUASAN PASIEN TERHADAP CITA RASA MAKANAN DENGAN LAMA HARI RAWAT DI RUMAH SAKIT UMUM WISMA PRASHANTI TABANAN - Ni Ketut Mariasih; Anak Agung Nanak Antarini; Ida Ayu Eka Padmiari (Jurnal Ilmu Gizi : Journal of Nutrition Science, 2023)
Taste which includes the appearance and taste of food is one of the external factors that affect patient satisfaction and length of hospitalization. The success of nutrition services in inpatient rooms is related to the satisfaction of the patients served. Nutrition services in hospitals require a good and appropriate processing as a reference for quality services that can speed up the patient's healing process, shorten the length of stay, and save on treatment costs. , identifying the length of stay at the Wisma Prashanti Tabanan General Hospital and knowing the relationship between patient satisfaction with the taste of food and the length of stay at the RSU Wisma Prashati Tabanan. Methods Observational research with cross-sectional design. The research sample was 43 samples, which was carried out by purposive sampling. Analysis using fisher exact test obtained p value 0.05 which means that there is no relationship between patient satisfaction with food taste and length of stay at Wisma Prashanti Tabanan General Hospital. The conclusion of this study is that patients' satisfaction with the taste of food which includes the appearance and taste of food at theRSU Wisma Prashanti Tabanan, the sample states that they are satisfied with the taste of the food provided with a sample satisfaction value of 80.1%. The length of stay of patients at Wisma Prashanti Tabanan General Hospital in this study was an average of 2 days, there was no relationship between patient satisfaction with food taste and length of stay at RSU Wisma Prashanti Tabanan. Keywords: Patient Satisfaction, Food Taste, Length of Hospitalization